Prediction of sepsis progression in critical illness using artificial neural network - Suhaimi F.M.; Chase J.G.; Shaw G.M.; Jamaludin U.K.; Razak N.N. (Springer Verlag, 2023)
Biomarkers; Biomedical engineering; Decision making; Intensive care units; Neural networks; Antimicrobial therapy; Clinical guideline; Patient condition; Provide guidances; Sensitivity and specificity; Sepsis; Sepsis score; Septic shocks; Patient treatment